Aprendizagem experimental e jogos de empresas no estudo do mercado de capitais : uma aplicação - Freitas, Carlos Cesar Garcia (2007)
The organizations, nowadays, come across the adaptation challenge, front on the complexity of the inter-organizational relationships progress and the hard market competition, which is the result of a capitalist model development, markets integration, technology increment and the knowledge priority. The mentioned challenge is concerned with the creation capacity, diversification and innovation of products and services. Furthermore, this intricate situation implies more and more financial resources, and than, many organizations have been taking the capital market as receipts alternative, once it is in the great growth phase. However, it comes as a challenge to the Administration academic, once is a complex reality, which cannot be easily taught through methods and conventional techniques of teaching. The business game is one of the methodological tools to support the administration professionals' formation, based on the Kolb (1984) experiential learning methodology. Inside this context, this study object has been to model the conceptual and practical aspects, related to capital market, configuring a business game to assist pedagogically the skills developing process to administration students and analyzing the results. Therefore, an applied study has been accomplished, through quantitative method, defined in general as survey, and in a specific way as: technological, consisted in the creation of the business game and field, composed by the game application. The data collection, classified as transverse, has been realized using the questionnaire as research instrument, composed by eight assertive groups. Three of these groups delimit the sample profile, and the other five, evaluate the proposed game contribution, related to: the skills development (knowledge, ability and attitude), the participation satisfaction, and the evaluation of it, based on a 7 points Likert scale. The non-probabilistic sample, counting on 123 Administration students of the UNOPAR and UEL universities, both in Londrina-PR, was carried out in the 2006 second semester and 2007 first semester. The research was based on 4 applications of the developed game, and had as most important results: a) the JMC game has satisfactorily supported each one of the dimensions: knowledge, ability and essential attitudes in the skills development, resulted on a general evaluation of 4,7 points; b) working on the business games methodology was an improve and rewarding experience, resulting on a general evaluation of 5,4 points; c) the proposed JMC game was approved by the interviewees, and had a general evaluation of 5,3 points; and d) the JMC game contributes to the four learning styles involved in the study, with a general punctuation of 4,9 points. Adding to the detached results, we had the educator Nascimento's positive evaluation (2007), which considered the JMC game as an important tool to support the teachinglearning process on the capital market.